2016
DOI: 10.1371/journal.pone.0148514
|View full text |Cite
|
Sign up to set email alerts
|

IL-17a and IL-22 Induce Expression of Antimicrobials in Gastrointestinal Epithelial Cells and May Contribute to Epithelial Cell Defense against Helicobacter pylori

Abstract: Helicobacter pylori colonization of the human stomach can lead to adverse clinical outcomes including gastritis, peptic ulcers, or gastric cancer. Current data suggest that in addition to bacterial virulence factors, the magnitude and types of immune responses influence the outcome of colonization. Specifically, CD4+ T cell responses impact the pathology elicited in response to H. pylori. Because gastritis is believed to be the initiating host response to more detrimental pathological outcomes, there has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 73 publications
5
67
1
3
Order By: Relevance
“…S5) 14,15 . The functionally relevant induction of AMPs is consistent with studies in other tissues that also reported the induction of AMPs in response to IL-17 cytokines [47][48][49] . Of note is that AMPs also possess signaling functions for various cell types 50 .…”
Section: Discussionsupporting
confidence: 87%
“…S5) 14,15 . The functionally relevant induction of AMPs is consistent with studies in other tissues that also reported the induction of AMPs in response to IL-17 cytokines [47][48][49] . Of note is that AMPs also possess signaling functions for various cell types 50 .…”
Section: Discussionsupporting
confidence: 87%
“…Th17 cells producing their signature cytokines IL‐17A, IL‐17F, IL‐21, and IL‐22 approached the spotlight as they are linked to inflammation, but also to antimicrobial responses and the control of bacterial colonization. Recently, a synergistic action of IL‐17A and IL‐22 to induce antimicrobials and chemokines such as IL‐8, calprotectin, lipocalin, and β‐defensins in both human and primary mouse gastric epithelial cells and gastroids was proposed . In this study, IL‐22‐ and IL‐17A‐activated gastric epithelial cells were capable of inhibiting growth of H. pylori in vitro.…”
Section: Adaptive Immune Responsementioning
confidence: 78%
“…Reciprocally, activated ILC2s secrete IL‐13, which promotes tuft and goblet cell differentiation and parasite clearance . The signature cytokines secreted by Th17 cells (IL‐17A, IL‐17F and IL‐22) can also induce IEC‐mediated AMP secretion and reinforce IEC tight junctions . In addition, production of fibroblast growth factor 2 (FGF2) by Treg cells has recently been shown to synergize with IL‐17 to enhance mechanisms of intestinal epithelial repair .…”
Section: Iec–immune Cell Crosstalkmentioning
confidence: 99%